Volume 9: Oil and Gas Applications; Supercritical CO2 Power Cycles; Wind Energy 2017
DOI: 10.1115/gt2017-64958
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the Levelized Cost of Electricity of a Concentrating Solar Power Tower With a Supercritical Carbon Dioxide Power Cycle

Abstract: In order to maintain viability as a future power-generating technology, concentrating solar power (CSP) must reduce its levelized cost of electricity (LCOE). The cost of CSP is assessed with the System Advisor Model (SAM) from the National Renewable Energy Laboratory (NREL). The performance of an integrally geared compressor-expander recuperated recompression cycle with supercritical carbon dioxide (sCO2) as the working fluid is modeled. A comparison of the cycle model to the integrated SAM cycle performance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Two different dispatch control schemes are considered in this work: the default scheme reported by SAM and the scheme proposed by the SunShot Vision Study [28]. A graphical representation of these is presented in Figure 5 which confirms that these schemes merely define an overall schedule of plant operation but they do not substitute or interfere with the off-design control strategies described in another work from the same authors [11].…”
Section: Dispatch Control and Financial Modelmentioning
confidence: 54%
See 2 more Smart Citations
“…Two different dispatch control schemes are considered in this work: the default scheme reported by SAM and the scheme proposed by the SunShot Vision Study [28]. A graphical representation of these is presented in Figure 5 which confirms that these schemes merely define an overall schedule of plant operation but they do not substitute or interfere with the off-design control strategies described in another work from the same authors [11].…”
Section: Dispatch Control and Financial Modelmentioning
confidence: 54%
“…With this in mind, it is concluded that more accurate part-load models and integration schemes in SAM or equivalent software will prove that either the Allam or Partial Cooling cycle layouts have the potential to make a strong case for the next generation of CSP plants based on sCO 2 power cycles, enabling the ambitious objectives targeted by the SunShot Program. In this regard, it is interesting to see how the selection of a particular set of assumptions (both financial, economic and thermal) has the potential to turn the Recompression cycle into a competitive option to achieve the 6 g/kWh target of the SunShot programme [28], which is certainly in contrast with the conclusions obtained in this work. Far from discussing the credibility of other research works, the latter statement aims to highlight that much more work on the assessment of appropriate sets of non-technical boundary conditions is still required.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Namely, a drop range of 15.6 to 67.7% in terms of CSP LCOE has been witnessed. Higher turbine inlet conditions and longer storage duration generally translate into lower LCOE, as can been seen from Ty Neises 117 , Yuegeng Ma 118 , J. Schmitt 119 . However, it is not always right under the circumstance that higher operating conditions call for higher corrosion-resistance materials such as nickel based alloys instead of commonly used stainless steel, as summarized before.…”
Section: Economic Analysis and Comparison Of The Integrated Systemmentioning
confidence: 94%
“…The annual simulation is performed using the System Advisory Model (SAM V2018.11.11), which designs a heliostat field layout optimised for the selected location of Dagget, California. A solar multiple of 2.8 and 14 hours of TES are used in this study [42]. SAM calculates the hourly optical efficiency and evaluates the energy absorbed by the HTF considering both the receiver and piping losses.…”
Section: Solar Fieldmentioning
confidence: 99%